تحديد انتالبيات تشكل المركبات التيوايتيرات الحلقية الثلاثية حتى السباعية غير المتجانسة في الحالة الغازية بالطرائق النظرية المختلفة عبر طاقات التذري ومخططات فصل الروابط (Latakia University Journal -Basic Sciences Series, 2017)
تم تحديد انتالبيات تشكل المركبات التيوايتيرات الحلقية الثلاثية حتى السباعية 11) مركباً( في الحالة الغازية بالطرائق المركبة Gn وCBS، والسويتين النظريتين و من خلال التقريبين: طاقات التذري (AE) ومخططات فصل الروابط (BS). حدد الانحراف الوسطي المطلق (MAD) والانحراف القياسي (SD) للمعطيات النظرية عن القيم التجريبية. لوحظ أن طريقة فصل الروابط تقدم انحرافات وسطية مطلقة لمعظم الطرائق النظرية مقارنة بتقريب طاقة التذري؛ إذ تقدم السوية النظرية G3MP2 اقل قيمة لـ MAD، في حين تكون الانحرافات الموافقة للسويتين النظريتين و قريبة من انحرافات الطرائق المركبة. لا تبدي المجموعة الأساسية 6-31g(d,p) تأثيراً جوهرياً في النتائج النظرية.Enthalpy of formation for three- and seven- membered heterocyclic theoethers (11 compound) in gas state have been determined by different theoretical methods: compo-site methods (Gn, CBS) and two levels of theory and via two approaches: atomization energy (AE) and bond separation (BS). Median abs-lute deviations (MAD) and standard deviations (SD) of calculation values from experi-ment data have been determined for every used theoretical method. It has been observed that the bond separation approach produce lower value of MAD in most of the theoretical methods in comparison to the atomization energy approach; where the G3MP2 method produce lower value of MAD, while the deviations corresponding to the two levels of theory and is close to the deviations of the composite methods. The basic set doesn't show substantial effect in the theoretical results.